PENGEMBANGAN E-MODUL SEJARAH MATEMATIKA BERORIENTASI BERPIKIR PENALARAN SEBAGAI INOVASI PEMBELAJARAN PADA MAHASISWA TADRIS MATEMATIKA - Miftahul Fitri; Anas, Marnisyah; Mariana, Sri; Kalsum, Umi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to develop a reasoning-oriented history of mathematics e-module for second-semester students of the Tadris Mathematics Study Program at Universitas Islam Sarolangun and to determine its validity, practicality, and effectiveness. This study employed a Research and Development (R&D) method using the ADDIE development model, which consists of analysis, design, development, implementation, and evaluation stages. The research subjects consisted of expert validators and second-semester students of the Tadris Mathematics Study Program at Universitas Islam Sarolangun. Data were collected through observations, interviews, questionnaires, mathematical reasoning tests, and documentation. The data were analyzed descriptively using quantitative and qualitative approaches with a Likert scale. The results showed that the developed e-module obtained an average validity score of 88.25% categorized as very valid and an average practicality score of 91% categorized as very practical. The effectiveness test indicated that the e-module was effective in learning activities with a classical completeness percentage of 82.35%. The reasoning-oriented history of mathematics e-module developed in this study is feasible to be used as an innovative digital teaching material to facilitate students’ mathematical reasoning abilities in History of Mathematics learning.